Trials and tribulations of students writing their own textbook - Fairweather, Helen (University of the Sunshine Coast, 2015)
The RStudio package provides a vehicle for students to implement analyses relevant to hydrology. By using the “knitr” package, students can create a living and dynamic document that embed these analyses into a text editor. This text andrelevant analyses and compiled to create a web page, pdf or word document. When underlying data changes, or the methods are updated, the student has at their finger-tips, analyses techniques that can be re-run. The representation of the ‘text-book’ is updated to this changed situation. Several difficulties have been experienced implementing this project, with the major problem being the prior lack of exposure to the programming language approach. Development of this skill is critical for hydrology students, but, as evidenced by the results of early surveys in this project, this is often not clear to students. Students are provided with templates with both text and analyses (called chunks) and they are required to add to the templates in the form of the notes they take. These notes can be entered directly into the text document during the class, or if hand-written notes are taken, the student can take a photo and embed the photo in the document they produce. In the document supplied to the student, not all analyses are complete, and the students are expected to implement the missing parts. The templates provided to the students are broken up into modules, and to create the complete document they need to be ‘knitted’ together. This has proven to be a problematic step. One of the major hurdles faced is students do not seem to be familiar with how to change the pointers to the directories in the supplied templates. It is explained that it is important to change these directories to match the structure on their computer, but this step is often missed. As RStudio is able to easily import relevant hydrology data from many sources, the ability to display these data in a variety of configurations should enhance the student’s learning. But much like the problems faced above, it is difficult to get student’s through the learning curve of implementing the code to conduct the analyses. To facilitate this, a combination of Excel and RStudio are used to explain the concepts. This works well, where two screens can be shown to the students at the same time, which is the case in the Immerse Lab and the Collaboration Studio in the Engineering Learning Hub.